Geographical distribution of Brucella melitensis inferred from rpoB gene variation - Kim-Kee Tan; Yung-Chie Tan; Li-Yen Chang; Kok Wei Lee; Siti Sarah Nor'e; Wai-Yan Yee; Chee-Choong Hoh; Sazaly AbuBakar (Journal of Infection in Developing Countries)
Introduction: Currently available tests have limitations for the identification of Brucella species and strains, and their genetic lineage. The genome sequence of the rpoB gene encoding the β-subunit of DNA-dependent RNA polymerase was investigated for its use in genotyping Brucella melitensis.